THE SOCIO-CULTURAL CONSTRAINTS IN THE IMPLEMENTATION OF POLITENESS STRATEGIES IN THE INTERACTIONS AMONG ENGLISH LANGUAGE EDUCATION STUDENTS - Suwartama, I Made; Fitriati, Sri Wuli (Universitas Negeri Semarang, 2017)
This study aimed to investigated socio- cultural constraints in the implementation of politeness strategies in the interaction among English Graduate Students. This study used discourse analytic approach by involving 30 participants. Source of the data: students’utterances. Methods of collecting data: recording, transcribing and questionnaire. Techniques of analysing data: identifying, categorizing, interpreting, and tabulating. To achieve the trustworthiness used triangulation. The findingsshowed 16 aspects of social constraints: 3 social status (18.75%), 2 social environment (12.5%), 2 family status (12.5%), 2 economy/financial (12.5%), 1 social determinant of health (6.25%), 1 adverse childhood experience (6.25%), 3 social relationship (18.75%), 2 kinship system (12.5%).There were18 cultural aspect constraints: 2 perceptions (11.11%), 2 motivations (11.11%), 3 experiences (16.67%) , 2 emotional (11.11%), 3 cultures (16.67%), 2 physical (11.11%), 2 linguistics (11.11%), and 2 nonverbal (11.11%). The total number of positive politeness were 65 aspects of positive politeness and 39 kinds of negative politeness. The cultural aspect constraints appeared more frequently than social aspect constraints. Positive politeness strategies appeared more frequently than negative politeness strategies. It can be concluded that the participantsmostly used politeness strategies to redress the addressee’s positive face.